Agent simulation of vessels traveling in sea - Zhang, Huiliang (2008)
The objective of our project is to design an agent architecture to simulate the intelligence and behaviour of a vessel captain in navigation. An agent representing a vessel captain should be able to perceive the environment, make decisions and act simultaneously. The agent should be able to prioritize its activities according to their importance and urgency. The agent should be able to reconsider its goals and intentions and adapt in the changing environment. The agent should be able to improve its performance with the accumulation of experience. Different vessel captains and thus different vessel agents should behave differently based on different personalities and past experience. It is also the objective of our research that work done here is general enough for building agents in other contexts like a robot looking after a patient or old people.